Improving the reliability of water service delivery in rural Kenya through professionalized maintenance: a system dynamics perspective - Chintalapati, P; Nyaga, C; Walters, JP; Koehler, J; Javernick-Will, A; Hope, R; Linden, KG (American Chemical Society, 2022)
Reliable water service delivery continues to be a complex global issue that is particularly challenging in rural communities. Despite billions of dollars of infrastructure interventions, sustainable water services remain out of reach for millions of people. Professionalized maintenance services have emerged as a service provision strategy to supplement the community-based rural water management approach. This study applies system dynamics modeling to assess the potential impact of scaling up professionalized maintenance services on piped water systems in Kitui County, Kenya. The study results show that over a 10 year simulation, calibrated with 21 months of empirical data and based on a range of key assumptions, delivery of professionalized maintenance services across the county may increase countywide functionality rates from 54% to over 83%, leading to a 67% increase in water production. Furthermore, the increase in preventive maintenance activities and proactive repairs can lead to less frequent major breakdowns and reduction in county government spending on major repairs by over 60%. However, current service fee income from communities accounts for 8% of the total cost of service, necessitating substantial sustained external financing or government subsidies to be financially viable at scale.